The Role of The Land Deed Officials in Mortgage Right Credit Agreement in PT. Bank Jateng Branch Slawi, Tegal Regency - Dimas Sakti Wardhana; Tegar Firmansyah; Aryani Witasari (Jurnal Akta, 2018)
This study aims to determine the implementation of Credit Agreement with the guarantee of Mortgage Right made by Notary of Land Deed Officials at PT. Bank Jateng Branch Slawi, Tegal Regency, to know the role of Notary Land Deed Officials, to know the constraints faced by Notary and what the solutions can be considered to solve the problem. This legal investigation included a descriptive type of empirical legal research. Research location was at PT. Bank Jateng Branch Slawi, Tegal Regency and the Notary office of Dewi Milasari, S. Sos., S.H., M.Kn as Notary PPAT partner. Based on this research, it found that credit granting mechanism in PT. Bank Jateng Branch Slawi, Tegal Regency is done through 5 stages: stage of loan application, credit analysis, credit decision, credit agreement and credit binding stage. Before credit agreement is executed, Notary as a partner is obliged to check the validity of guarantee of Mortgage Rights, Notary PPAT in credit agreement with guarantee of Mortgage right provides legal certainty for parties holding credit agreement. The constraint faced by Notary in making credit with Mortgage Right is the credit agreement draft which has been prepared by bank (creditor). However, the contents are unfair or more disadvantageous to the customer (the debtor), and the banking party often (creditor) absent in the signing of the deed.Keywords: Role of Land Deed Officials; Credit Agreement; Mortgage Rights